Implementation of an Integrated Mobile Livestock Service Program at The Livestock and Animal Health Department of Aceh Province - Mustaqim, Mustaqim; Sari, Wenny Novita; Fajri, T. Irfan (Devotion : Journal of Research and Community Service, 2023)
Implementation is the process of carrying out new ideas, programs, or a set of activities with the expectation that others can accept and make changes, conveying several messages, ideas, or concepts through the process carried out by an individual in the sense of human relationships or what is called human relations. Mobile services are one of the implementations that can be applied to livestock information and health management programs. The objective of this research is to determine the implementation of the Integrated Mobile Livestock Service Program at the Livestock and Animal Health Department of Aceh Province. The research approach used in this study is qualitative, which examines the object and reveals existing cases contextually through collected data. Each district surveyed includes 50 people for this mobile cow service program. The observed aspects of this program include: Public complaints about livestock diseases through the application, Interest in using health service information on the application, Public satisfaction with the application. The research results indicate that the complaints found in the community are about scabies and FMD (Foot-and-Mouth Disease). However, these complaints are obtained directly from the community, and only a few come through the application. The average application visitors in Pidie district are 29.87, Bireuen district 29.03, Aceh Utara district 27.47, Aceh Timur district 30.77, and Langsa city 29.33. User satisfaction with the application is assessed through questionnaires given directly to the community. The survey results show that, on average, people still have a limited understanding of the application's usage and are not very satisfied.